Cryopreserved Mesenchymal Stromal Cells In Experimental Oophoritis Therapy - Yukhta, Mariya S.; Volkova, Nataliya A.; Stepanyuk, Lyudmila V.; Chernyshenko, Lyudmila G.; Goltsev, Anatliy N. (Problems of Cryobiology and Cryomedicine, 2016)
Probl Cryobiol Cryomed 2016; 26(2):169.